To what extent can Facebook be useful for small and medium-sized enterprises (SMEs) in relation to their business growth - Yong, Zi Ming (2016)
This research examines to what extent SMEs can gain benefits from the use of social media, particularly Facebook. Although it has been used by many organizations and users throughout the world to gain a competitive edge, little attention has been given by small and medium-sized enterprises (SMEs) in the use of Facebook to grow their businesses. Therefore, to investigate the usefulness of Facebook for SMEs in growing their businesses, three semi-structured face-to-face interviews with three entrepreneurs were conducted in the University of Nottingham Ingenuity lab. This qualitative research method highlights a few interesting findings about the use of Facebook in businesses. It was found that all or the participants were willing to use Facebook in their business. The reason is because the young entrepreneurs believed the benefits acquired from Facebook far outweigh the costs. It is noticed that knowledge is no longer perceived as the costs of using Facebook for young entrepreneurs and their attitude towards Facebook is different in newer generations. It also identified that the nature plays a significant role in the use of Facebook. Also, it demonstrated that the population mix and the issue of trust were the main factor affecting the use of Facebook. As a whole, it demonstrated a different understanding of how Facebook is perceived as compared to previous study.